2018
DOI: 10.18662/rrem/61
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Perceptions on the Relevance of Specific Health Education Topics in School

Abstract: This paper illustrates the results obtained through the analyzing of the teachers' feedback , expressed at the graduation moment of the accredited training program "Modern Approaches in Health Education", organized in the frame of the Erasmus+ project "Let's make it better! Raising the awareness of the triad nutritionhealth-food safety in school education", coordinated by Valahia University Targoviste, Romania. Two Modules and 8 related topics were designed, consisting in 18 hours of courses and 36 hours for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“… 8 Primary and secondary school educators in Romania reported that food hygiene and related risks was one of the most important topics that they, as educators, wished to learn in the context of nutrition and health and food safety. 21 …”
Section: Discussionmentioning
confidence: 99%
“… 8 Primary and secondary school educators in Romania reported that food hygiene and related risks was one of the most important topics that they, as educators, wished to learn in the context of nutrition and health and food safety. 21 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous researches (Damian, Oltean & Damian 2018), (Gorghiu, Buruleanu, Gorghiu, & Avram, 2018), (Marchuk, Chemerys, 2018) (Yablochniuk, Zymovets) and others show and prove that the problem of forming children's health-saving competence is getting higher.…”
Section: Health-saving Competence In the Educational Processmentioning
confidence: 99%
“…Ele acoperă o paletă largă din cadrul tematicii sănătății și dezvoltării, ca lungime, de la texte mai condensate (Borca, 2010;Nadolu, 2020;Ștefănescu, 2016;) la analize detaliate (Berbecar et al, 2020;Druică et al, 2019;Saghin, Lucheș, Marici, 2016). Ele se axează fie pe o temă mai în detaliu (Bunt et al, 2020;Dumitrache et al, 2020;Mihalache, Apetroi, Tomaziu-Todosia, 2019), fie oferă atenție mai multor subiecte (Gorghiu et al, 2018;Sergentanis et al, 2021;Tomaziu-Todosia, 2019).…”
Section: Metodologieunclassified
“…Studiind un eșantion de studenți din România, Năsui et al (2021) subliniază importanța unor campanii sanitare care să promoveze un stil de viață sănătos și echilibrat. În urma aplicării unui chestionar, Gorghiu et al (2018) identifică concepte ale educației alimentare care ar trebui introduse în învățământul preuniversitar. Baiocco et al (2021) analizează nevoia de a introduce strategii de informare a personalului medical din șapte țări europene despre nevoile medicale specifice comunității LGBT+.…”
Section: Cercetări Despre Aspecte Teoretice Istorice Legislație Starea Sistemului Medical șI Aspecte Ale Societățiiunclassified